Some aspects of primary black holes in the early Universe and inflationary cosmology - Shalyt-Margolin, Alexander E. (Journal of the Belarusian State University. Physics, 2023)
Primary black holes can arise in the early Universe irrespective of what cosmological scenario of its expansion (inflationary, cyclic or other) is realised. However, the very existence of these objects can change the basic parameters of the above scenario if they arise before the beginning of its realisation, i. e. in first moments after the Big Bang. Therefore, the investigation of the formation and evaporation of primary black holes is a powerful tool to study the processes in the early Universe, in particular, the gravitational collapse, various cosmological models, and also high energy physics. At present these black holes are studied most often within the semiclassical approximation, i. e. in the case when the secondary quantised fields of matter are considered against the classical space-time background. But since energies at which primary black holes arise often are close to Planckian energies, such consideration cannot be considered satisfactory, since in this case quantum-gravitational effects become essential. This paper demonstrates the ways to include the quantum-gravitational corrections generated by this effects in inflationary cosmological models if primary black holes arise in the preinflationary epoch. It is shown that, due to the validity of the generalised uncrtainty principle, these corrections may be calculated for all the fundamental inflationary parameters, specifically, for the scale factor, Hubble parameter, slow roll parameters, etc.